Language Relations and Cultural Rituals: An Ethnolinguistic Study on Traditional Wedding Ceremonies (Trang Kampung) - Niken Ardila Rehiraky (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study explores the intricate relationship between language and cultural rituals through an ethnolinguistic examination of traditional wedding ceremonies on Kisar Island, Indonesia. Traditional wedding rituals serve not only as celebratory events but also as mediums to preserve and transmit cultural values, identity, and social norms. The study highlights how language is employed as a vital tool for conveying symbolic meanings, maintaining traditions, and reinforcing ethnic identity. Utilizing a qualitative ethnographic approach, the research captures the linguistic and cultural dimensions of the Kisar wedding ceremony, focusing on specific elements such as the Konoknohi (notification of happy news), Raikorwuku (family gatherings), and Trang Kampung (wedding processions). Findings reveal that language serves multifaceted roles, including as a means of communication, a marker of social structure, and a reflection of collective identity. Key linguistic practices, such as the use of opening greetings, ritual speeches, and symbolic terms, are shown to embody respect, unity, and cultural continuity. Moreover, the study emphasizes the symbolic significance of material contributions (Takuraram), ritual activities like drinking sopi, and gestures such as nose-kissing, which collectively foster familial harmony and solidarity. By analyzing these linguistic and cultural elements, the research provides valuable insights into how traditional rituals sustain cultural heritage and social cohesion across generations. This ethnolinguistic perspective contributes to broader understandings of the interplay between language, culture, and identity within the context of traditional practices.